2016
DOI: 10.1007/s13277-016-5388-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-218 inhibits the proliferation, migration, and invasion and promotes apoptosis of gastric cancer cells by targeting LASP1

Abstract: The present study aims to investigate the effects of microRNA-218 (miR-218) on the proliferation, migration, invasion, and apoptosis of gastric cancer (GC) cells by targeting LIM and SH3 domain protein 1 (LASP1). The GC cells in the logarithmic phase were selected and divided into five groups: the blank group, negative control (NC) group, miR-218 inhibitors group, miR-218 inhibitors + siLASP1 group, and miR-218 mimics + siLASP1 group. The miR-218 expression in each group was also detected by qRT-PCR. The CCK8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Previous studies have demonstrated that miRNAs negatively regulate target gene expression by binding to the 3'UTR of target genes (26)(27)(28). In the present study, MTDH was identified as a novel target gene of miR-154 in GC.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have demonstrated that miRNAs negatively regulate target gene expression by binding to the 3'UTR of target genes (26)(27)(28). In the present study, MTDH was identified as a novel target gene of miR-154 in GC.…”
Section: Discussionsupporting
confidence: 51%
“…MiR-218 upregulation inhibited the proliferation and invasion and induced apoptosis of pancreatic cancer cells [30]. Interestingly, miR-218 could suppress cell proliferation, migration and invasion in gastric cancer and prostate cancer [31,32]. Moreover, our gene microarray analysis showed that ANLN downregulation induced miR-218 expression.…”
Section: Introductionmentioning
confidence: 97%
“…A previous study reported that >50% of known miRNAs are located at genomic regions or in fragile sites closely correlated with cancer (11). Additional studies reported that miRNAs were abnormally expressed in a variety of human cancers, such as HCC (12), gastric cancer (13), colorectal cancer (14), glioma (15) and bladder cancer (16). These dysregulated miRNAs may act as oncogenes or tumor suppressors in tumorigenesis and tumor development, which depends on tumor type and the roles of their target genes (17,18).…”
Section: Introductionmentioning
confidence: 99%